Menanamkan Nilai-Nilai Kewirausahaan pada Anak Usia Dini - Marini Marini (Atfaluna: Journal of Islamic Early Childhood Education, 2019)
The purpose of this research is to describe how to embed entrepreneurial values in early childhood in Kudus. This research was conducted by research method of survey on 36 early childhood educational institution in Kudus in academic year 2017/2018. Data collection techniques are conducted with questionnaire techniques, observations, and interviews. Entrepreneurship education in early childhood educational institution in Kudus aims to foster an entrepreneurial interest and instill social values, economic value, creativity, forming a patient person, appreciating hard-earned, appreciating their own work, disciplined, independent, and responsible. The activity of the planting of entrepreneurial values in early childhood in Kudus is carried out with diverse strategies, ranging from observation to the entrepreneurial places, playing the role of buying and selling, direct buying and selling practices, making something that can be for sale, livestock and farming. Such activities require adequate time, place, and energy. Thus it needs to be planned maturely, so that the implementation of learning runs effectively.